Edukacja ewangelicznych chrześcijan w Polsce w okresie międzywojennym - Skotarczak, Dorota (Biuletyn Historii Wychowania, 2014)
The second half of the 19th century in Russia was marked by the emergence of an evangelical movement out of which emerged the evangelical Christians (ewangeliczni chrześcijanie). This protestant group spread gradually on Polish territory. Between WW I and WW II, there were many centres of evangelical Christians, especially on the eastern side of country. Evangelical Christians had schools with special syllabuses. In these schools they educated priests, missionaries and conductors of church choirs. These schools were also very important theological centres.